Parasite fauna of Periplaneta americana Linnaeus district in Lima - Iannacone, José (1999)
We conducted a research on some community components and infracommunities of parasite fauna of American cockroach, P americana, on one hundred specimens collected from the sewage of the district of Pueblo Libre, Lima-Perú, between August and September 1996. Of the cockroachs collected 67 were male and 33 female, 19 were adults and 81 early instars. The cockroachs were necropsied and we found five parasites with prevalence and intensity of infection as follows: Cephalobellus tipulae (Nematode) (38%, 3,5), Leidynema appendiculatum (Nematode) (35% y 2,85), Thelastorna bulhoesi (Nematode) (1% y 7), Moniliformes moniliformes (Acanthocephala) (2% y 1,5), and Pimeliaphilus cunliffei (Acarina) (62% y 5,03). P cunliffel was considered a core species; C. tipulae and L. appendiculatum were secondary species and M. moniliformis and 7 bulhoesi were satellite species. C. tipulae and L. appendiculatum had high values of frequency of dominance. In general, there was no correlation between intensity and prevalence of parasites and lenght and sex. The parasite's biodiversity is low H' = 0,397 t 0,45. C. tipulae and L. appendiculatum showed a negative covariation and interspecific association, T bulhoesl and P cunliffei are new records to Peru.